2013
DOI: 10.1177/193229681300700130
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Applications for Diabetes Self-Management: Status and Potential

Abstract: Research into the adoption and use of user-centered and sociotechnical design principles is needed to improve usability, perceived usefulness, and, ultimately, adoption of the technology. Proliferation and efficacy of interventions involving mobile applications will benefit from a holistic approach that takes into account patients' expectations and providers' needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
264
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 330 publications
(303 citation statements)
references
References 41 publications
15
264
0
7
Order By: Relevance
“…These are also the most common features in U.S. diabetes apps, 12,26 supporting the generalizability of our findings. However, few apps included more than 12 of the 15 self-management features, and seven of the apps had none, suggesting that few of the apps could provide a comprehensive set of tools for diabetes self-management.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…These are also the most common features in U.S. diabetes apps, 12,26 supporting the generalizability of our findings. However, few apps included more than 12 of the 15 self-management features, and seven of the apps had none, suggesting that few of the apps could provide a comprehensive set of tools for diabetes self-management.…”
Section: Discussionsupporting
confidence: 69%
“…Evidence suggests that information about laboratory tests, CAM, healthcare providers, and psychosocial support are all important to patients. [23][24][25] Information about psychosocial support, for example, affects patients' well-being, 12,26,28 and psychosocial interventions can improve patients' diabetes self-management. 1,3,8,29 Not providing information about the psychosocial aspects of diabetes self-management is a missed opportunity that should be addressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Se ha demostrado que estos dos factores desempeñan un papel fundamental en la adherencia a la prescripción, así como en el fomento exitoso de un estilo de vida sana y otros cambios de conducta (Heneghan et al, 2013). Un plan de educación personalizada es indispensable para proporcionarle al paciente las herramientas adecuadas que necesita para la autogestión efectiva de la enfermedad (El-Gayar et al 2013).…”
Section: La Motivación Y Atribución De Poder De Los Pacientes Son Quiunclassified
“…It has been demonstrated that these two factors play an essential role in prescription adherence, as well as for the successful encouragement of a healthy life-style and other behavioural changes (Heneghan et al 2013). A personalised education plan is indispensable in order to provide the patient with the appropriate tools needed for the effective self-management of the disease (El-Gayar et al 2013). …”
Section: A Technological Framework Based On Automatic Messaging For Imentioning
confidence: 99%